Pengaruh Relaksasi Napas Dalam Terhadap Kecemasan Ibu Preoperatif Sectio Caesarea Di Rumah Sakit - utami, rina; Nonok Karlina; Pipit Indra Lestari; Rosiyana Amila (LPPM ITEKES Mahardika, 2026)
Introduction: Preoperative anxiety in mothers undergoing sectio caesarea is a common psychological condition that may negatively affect maternal readiness and surgical outcomes. Midwifery care requires effective non-pharmacological interventions to manage this condition. This study aimed to determine the effect of deep breathing relaxation on anxiety levels among preoperative sectio caesarea mothers. Method: A pre-experimental design with a one group pretest-posttest approach was applied. A total of 40 respondents were selected using total sampling. Anxiety levels were measured using the Amsterdam Preoperative Anxiety and Information Scale (APAIS). Data were analyzed using the Wilcoxon test. Result: The results showed that prior to the intervention, most respondents experienced panic-level anxiety (45%), while after the intervention, the majority reported mild anxiety (82.5%). Statistical analysis indicated a significant effect (p-value = 0.000; p<0.05). Conclusion: Deep breathing relaxation effectively reduces anxiety and can be integrated into holistic midwifery care to improve maternal psychological readiness before surgery.